If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 2(y + -9) = 5(y + 1) + -4 Reorder the terms: 5y + 2(-9 + y) = 5(y + 1) + -4 5y + (-9 * 2 + y * 2) = 5(y + 1) + -4 5y + (-18 + 2y) = 5(y + 1) + -4 Reorder the terms: -18 + 5y + 2y = 5(y + 1) + -4 Combine like terms: 5y + 2y = 7y -18 + 7y = 5(y + 1) + -4 Reorder the terms: -18 + 7y = 5(1 + y) + -4 -18 + 7y = (1 * 5 + y * 5) + -4 -18 + 7y = (5 + 5y) + -4 Reorder the terms: -18 + 7y = 5 + -4 + 5y Combine like terms: 5 + -4 = 1 -18 + 7y = 1 + 5y Solving -18 + 7y = 1 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -18 + 7y + -5y = 1 + 5y + -5y Combine like terms: 7y + -5y = 2y -18 + 2y = 1 + 5y + -5y Combine like terms: 5y + -5y = 0 -18 + 2y = 1 + 0 -18 + 2y = 1 Add '18' to each side of the equation. -18 + 18 + 2y = 1 + 18 Combine like terms: -18 + 18 = 0 0 + 2y = 1 + 18 2y = 1 + 18 Combine like terms: 1 + 18 = 19 2y = 19 Divide each side by '2'. y = 9.5 Simplifying y = 9.5
| 27x-9=-4+49 | | -4x-3+8x=21 | | 92=-4(1-3a) | | -6x+17=-6x-36+6 | | 5xn=120 | | 37+5m=-7(1-7m) | | 45+9= | | 3x+17=3+7x | | 6*5+3y=15 | | 6xy+9y=30 | | 9x+7+8x-2=90 | | x+16.45=10+15 | | 22.85+19x=21.95+18x | | X+(x+2)=1500 | | x+1+5x=19 | | 8x+2y-13=0 | | .25x+5=9 | | 190=5(3v+-7)+10v | | -2x^2+3x+14=0 | | -6(k+1)=-3-6k-3 | | 3(11r-13)=7r+57+32r | | 4+3x=x+14 | | x+15=10+16.45 | | 48-48-3(x-4)=3x | | -y-1=2y-16 | | 9x^2-45x+36=0 | | 3-0.25x=-0.5x+9 | | 75-2q=-15+4q | | -21+5(8-4)= | | .90+19x=18x | | 6x^2-54x+120=0 | | 2x-3=-3x-2 |